Lowering of the water table in the urban spaces of the city of Montes Claros-MG (Research, Society and Development, 2022)
The population increase in the city of Montes Claros (MG) in Brazil, added to the low rainfall, the poor distribution of the rain during the year, amplified by the exacerbated use of water in irrigation and the geological characteristics of the region, result in frequent situations of scarcity of water, consequently, an expressive exploration of the water volume of the water table of the urban area and its surroundings. In this sense, the main objective of the article was to evaluate the exploitable volume of water for urban supply. Throughout the development of the article, the expressive population growth was listed, between the years 1975 to 2020, it increased from 125.216 to 413.487 inhabitants. And in the same period, the consumption flow changed from 1.007,33 m³/h to 3.326,40 m³/h. The identification of existing underground wells in the study location was based on the Groundwater Information System database – SIAGAS. Of the 2,031 registered wells, 1,033 are equipped, 303 pumping, 204 not installed, 117 abandoned, 74 stopped, 28 not usable, 25 dry, 9 closed and 238 without data. Among these, 154 tube wells were selected (76 in the urban area and 78 in the rural area), given the availability of lithological profile data. From the analysis of the depth of the water table, the Static/Dynamic levels of the wells, it was verified that the lowering of the water table is taking place, inferring from the exploitation of groundwater and the waterproofing of the soil. Finally, it is necessary to explore water consciously by the whole society and the need for conservation actions by everyone, immediately.